Digital economy for customer benefit and business fairness : proceedings of the international conference on sustainable collaboration in business, information and innovation (SCBTII 2019), Bandung, Indonesia, October 9-10, 2019 /: proceedings of the international conference on sustainable collaboration in business, information and innovation (SCBTII 2019), Bandung, Indonesia, October 9-10, 2019. (2020) - Unknown
No abstract available